Effects of bicarbonate on oxyhaemoglobin desaturation and exercise performance in athletes - Do Valle Bargieri, J.; Berton, D. C.; Aparecido De Almeida, A.; Asprón Garcia, F.; Carlos Da Silva, A.; Alberto Neder, J.; Andrade, M. S. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: Decrease in peripheral oxygen delivery may impact exercise performance in athletes with exercise-related arterial oxygen desaturation (ERD). We evaluated whether sodium bicarbonate ingestion would be effective to reduce ERD and what is the consequences upon exercise performance. Methods: Seventy highly trained athletes performed an incremental treadmill cardiopulmonary exercise test (incCPX) and a high intensity constant speed test (ctCPX) on separate days. Subjects who developed ERD by pulse oximetry were randomly allocated to oral sodium bicarbonate or placebo during 5 days. At the end of treatment subjects repeated both tests. Results: ERD prevalence was 33% during the incCPX (17 % severe, 48% moderate and 35% mild) and 34% (5 % severe, 37% moderate and 58% mild) in the ctCPX. Athletes who developed ERD have greater aerobic capacity (incCPX) and endurance time (ctCPX). Active treatment, but not placebo, reduced ERD during ctCPX (P0.05). Conclusion: Sodium bicarbonate was effective in lessening ERD during ctCPX in athletes. However, this intervention failed to improve maximal and submaximal exercise capacity in these subjects.